Sintesis katalis asam heterogen berbasis polivinil alkohol (PVA) dan pemanfaatannya dalam produksi metil ester asam lemak - Hartono, Ryan; Muljana, Henky; Sugih, Asaf Kleopas; Oemar, Usman; Atin, Jessica; Ahimsa, Gadmon (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2023)
Sulfonated polyvinyl alcohol is a potential heterogeneous acid catalyst for fatty acid methyl esters (FAME) production. The catalyst (PVA/SSA) was synthesized via an esterification reaction between polyvinyl alcohol (PVA) and sulfosuccinic acid (SSA). This research aimed to study the effect of several process variables, such as the molecular weight (MW) of PVA, washing step with methanol, annealing conditions (time, temperature, and annealing pressure), and drying temperature on the performance of the PVA/SSA catalyst in methanol and free fatty acid (FFA) esterification. The sulfonated PVA catalyst was successfully synthesized, as indicated by the presence of the sulfonate group (SO3) at an absorption band of 1267 cm-1 and the carbonyl group (C=O) at an absorption band of 1628 cm-1 in the FT-IR spectra. The resulting PVA/SSA catalyst shows a good performance, where maximum conversion of the fatty acid esterification reaction can reach 81.9%. In addition, the catalyst can be used for at least four repetitions with a decrease in FAME conversion from the first to the second stage of 28.2% and has relatively stable performance in the second and subsequent reactions (conversion range 49, 1% - 58.8%). The resulting catalyst also has good thermal stability with a first-stage degradation range of 200oC to 290oC, allowing it to be applied in a temperature range suitable to the FAME manufacturing industries requirement.